IMPLEMENTASI TUTOR SEBAYA DALAM KETUNTASAN BELAJAR MATERI BERWUDHU KELAS TINGKAT SEKOLAH DASAR - Elia Sari (IAIN Ambon, 2019)
Abstrack:The main purpose of educational progress was mastery learning. Although, sometimes mastery learning could not be reached maximally. It caused by the teacher used less precise method when they teach, student's lack of interest, uninteresting atmosphere, excessive student. However, it could be counter by teaching methods named “peer tutoring” this method placed students to teach other student in educational progress mastery teaching, in this method the teacher utilized the student’s potential as a kid and as a fellow student. In several studies, the effectiveness of peer tutoring to be used in learning methods so as improved mastery learning. Peer tutoring method in mastery learning worked as complement and assist, they did not replace the teacher’s duties, it made more flexible time for teacher so they could more focus on student’s learning needs. The application of peer tutoring in teaching method made learning situation more comfortable, interesting, active, and more prosocial interaction between students. The advantages and disadvantages are always present in every method, although with proper preparation the weakness could be minimized.